IMPROVEMENT OF CONTAINER TRANSPORTATION OF RAILWAY STATIONS OF THE REGIONAL RAILWAY HUB OF BUKHARA (World Bulletin of Social Sciences, 2024)
The purpose of this work is to determine the possibilities of performing cargo and commercial work in the organization of cargo transportation by container shipments, increasing their efficiency at the railway landfill of the Bukhara Regional Railway hub. Methods: Methods of system analysis are used. Results: Cargo and commercial operations performed by stations of the Regional railway hub of Bukhara are analyzed. Practical significance: The proposed mobile brigade creates favorable conditions for increasing local and foreign trade cargo flows in Uzbekistan. Organizing the work of such teams will increase the multimodality of the transport system of Uzbekistan and reduce traffic jams on highways, especially in large cities of Uzbekistan (improving the ecology of megacities).